2014
DOI: 10.1212/nxi.0000000000000012
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to MOG have a demyelination phenotype and affect oligodendrocyte cytoskeleton

Abstract: Objective:To examine the clinical features of pediatric CNS demyelination associated with positive myelin oligodendrocyte glycoprotein (MOG) antibodies and to examine the functional effects of MOG antibody on oligodendrocyte cytoskeleton.Methods:We measured MOG antibody using a fluorescence-activated cell sorting live cell-based assay in acute sera of 73 children with CNS demyelination (DEM) (median age 8 years, range 1.3–15.3) followed for a median of 4 years. We used MO3.13 cells to examine immunoglobulin (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
157
3
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 154 publications
(176 citation statements)
references
References 38 publications
14
157
3
2
Order By: Relevance
“…Anti-MOG antibodies occur more frequently in children than in adults and have been described (using different assays which, as noted above, may affect findings) in pediatric patients with a variety of autoimmune demyelinating disease phenotypes, including those of ADEM, MS, 32,[35][36][37] relapsing ADEM, relapsing ON, 38,39 relapsing ADEM-ON, 40 and relapsing ON-longitudinally extensive TM (NMO-like). 36,37 The normal function of MOG, which resides at the cell surface of oligodendrocytes, is not well understood.…”
Section: Cns-directed Antibodies In Pediatricmentioning
confidence: 99%
See 1 more Smart Citation
“…Anti-MOG antibodies occur more frequently in children than in adults and have been described (using different assays which, as noted above, may affect findings) in pediatric patients with a variety of autoimmune demyelinating disease phenotypes, including those of ADEM, MS, 32,[35][36][37] relapsing ADEM, relapsing ON, 38,39 relapsing ADEM-ON, 40 and relapsing ON-longitudinally extensive TM (NMO-like). 36,37 The normal function of MOG, which resides at the cell surface of oligodendrocytes, is not well understood.…”
Section: Cns-directed Antibodies In Pediatricmentioning
confidence: 99%
“…36,37 The normal function of MOG, which resides at the cell surface of oligodendrocytes, is not well understood. There is a dominant epitope involved in MOG IgG binding on the extracellular domain 13 and evidence of MOG IgG pathogenicity including alteration of oligodendrocyte cytoskeleton, 38 as well as implication in both complement-dependent and cell-based cytotoxicity. 35,41,42 A recent pathology report demonstrated antibody and complement deposition in an adult case of anti-MOG antibody-associated demyelination.…”
Section: Cns-directed Antibodies In Pediatricmentioning
confidence: 99%
“…7 We recently reported a remarkable elevation of myelin basic protein without glial fibrillary acidic protein detectable in the CSF of a patient with anti-MOG+ definitive NMO, suggesting myelin damage without astrocyte injury. 8 In common, both cases had anti-MOG positivity at the first event without any previous manifestation to induce exposition of central nervous system (CNS) antigens promoting a bystander phenomenon to produce autoantibodies.…”
Section: Discussionmentioning
confidence: 91%
“…(7/22), further strengthening the case that MOG antibody supports a non-MS diagnosis, although larger cohorts are required to further test this association. 30 Another study evaluated the frequencies of 57 of the newly identified non-HLA MS risk single nucleotide polymorphisms (SNPs) in 188 children with ADS, of whom 53 individuals had a subsequent diagnosis of MS. 31 In order to control the effect of genetic variation due to ancestry, only patients with European ancestry were included. Control groups were 456 patients with adult MS and 2,046 healthy adults.…”
Section: Genetic Background Associated Withmentioning
confidence: 99%